2020
DOI: 10.1177/1073274820924728
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prognostic Models for Patients With Penile Carcinoma

Abstract: Although penile carcinoma is a rare malignancy, there is still an unmet need to identify prognostic factors associated with poor survival. In this study, we utilized demographic and clinical information to identify the most informative variables associated with overall survival in patients with penile cancer. From a full model including all covariates found to be statistically significant in univariable analyses, we identified a parsimonious reduced model containing tumor site (penis glans: hazard ratio [HR] =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…29 However, two other groups identified young age as protective factors for survival. 27,28 Considering these nonsignificant and inconsistent results, we do not think age is a useful predictive factor for PSCC survival. In terms of tumor size and growth velocity, there were trends that large and fast-growing tumors might be related to poor prognosis.…”
Section: Lymph Vascular Invasionmentioning
confidence: 92%
“…29 However, two other groups identified young age as protective factors for survival. 27,28 Considering these nonsignificant and inconsistent results, we do not think age is a useful predictive factor for PSCC survival. In terms of tumor size and growth velocity, there were trends that large and fast-growing tumors might be related to poor prognosis.…”
Section: Lymph Vascular Invasionmentioning
confidence: 92%
“…Upon tumor progression, an up-regulation of CAV1 could then be observed, while stromal CAV1 expression levels decline, in particular in the fibroblastic compartment; effects that were found to be functionally relevant to tumor progression, invasion, metastasis and resistance to cancer therapeutic treatment (25,27,65). Invasive low-grade penile neoplasms are expected to have an excellent prognosis whereas invasive high-grade tumors (with regional or systemic dissemination) have a worse clinical outcome (19,20,66). Accordingly, we demonstrate that patients' survival significantly decreased with increasing tumor grades as well as increasing tumor stages, and that higher penile tumor grades (as well as higher tumor stages) were characterized by increased CAV1 expression levels within the malignant tumor cells while there was a significant loss of stromal CAV1.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive low-grade penile neoplasms are expected to have an excellent prognosis whereas invasive high-grade tumors (with regional or systemic dissemination) have a worse clinical outcome ( 19 , 20 , 66 ). Accordingly, we demonstrate that patients’ survival significantly decreased with increasing tumor grades as well as increasing tumor stages, and that higher penile tumor grades (as well as higher tumor stages) were characterized by increased CAV1 expression levels within the malignant tumor cells while there was a significant loss of stromal CAV1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated risk factors were also investigated and prediction models of patient survival were developed in the past years to achieve better management of this malignancy (15)(16)(17)(18). In all studies, lymph node involvement was found to be the most evidential factor (19) compared to other predictors including histological subtypes (20) and high expression levels of TP53-regulated inhibitor of apoptosis 1 (21). Although it is indicated that lymph node metastasis (LNM) could be roughly inferred from lymph node staging, lymph vascular invasion or sentinel lymph node biopsy combined with sonography (22)(23)(24), accurate prediction of lymph node status is still lacking and the connections between lymphatic metastasis and potential genetic biomarkers remain unclear (25).…”
Section: Introductionmentioning
confidence: 99%